Revealing tunnelling details by normalized differential conductance analysis of transport across molecular junctions. Issue 40 (2nd October 2017) - Vilan, A.
Abstract : A new analysis tool reveals hidden fingerprints of tunnelling mechanisms and quantifies the bias response via a scaling bias parameter. Abstract : This paper presents the use of normalized differential conductance (NDC) for exploring the effect of applied voltage on charge tunnelling across molecular junctions. It shows the power of NDC in revealing subtle features characteristic of specific tunnelling models and considers its theoretical basis in view of the Taylor-expansion (parabolic approximation) for tunnelling. A practical application of NDC is illustrated by analyzing the current–voltage relations across a short alkyl-thiol monolayer on smooth compared with rough Ag substrates.